Enzyme-assisted extraction of anthocyanins and other phenolic compounds from blackcurrant (Ribes nigrum L.) press cake: From processing to bioactivities. (15th October 2022) - Granato, Daniel; Fidelis, Marina; Haapakoski, Marjo; dos Santos Lima, Amanda; Viil, Janeli; Hellström, Jarkko; Rätsep, Reelika; Kaldmäe, Hedi; Bleive, Uko; Azevedo, Luciana; Marjomäki, Varpu; Zharkovsky, Alexander; et al.
Graphical abstract: Highlights: Blackcurrant press cake (BPC) was extracted with cellulase/beta-glucanase/pectinase. Enzyme-assisted extraction increased the recovery to phenolics and anthocyanins. BPC extracts showed no anti-inflammatory action in murine microglial cells. They had antiviral activity in Coxsackievirus A9 and human coronavirus HCoV-OC-43. They did not show cytotoxicity for normal and cancer human cells. Abstract: The effects of commercial enzymes (pectinases, cellulases, beta-1-3-glucanases, and pectin lyases) on the recovery of anthocyanins and polyphenols from blackcurrant press cake were studied considering two solid:solvent ratios (1:10 and 1:4 w/v). β-glucanase enabled the recovery of the highest total phenolic content – 1142 mg/100 g, and the extraction of anthocyanins was similar using all enzymes (∼400 mg/100 g). The use of cellulases and pectinases enhanced the extraction of antioxidants (DPPH − 1080 mg/100 g; CUPRAC – 3697 mg/100 g). The freeze-dried extracts presented antioxidant potential (CUPRAC, DPPH), which was associated with their biological effects in different systems: antiviral activity against both non-enveloped viruses (enterovirus coxsackievirus A-9) and enveloped coronaviruses (HCoV-OC43), and cytotoxicity towards cancer cells (A549 and HCT8). No cytotoxic effects on normal human lung fibroblast (IMR90) were observed, and no anti-inflammatory activity was detected in lipopolysaccharides-treated murine immortalised microglial cells.